Macrophage Polarization in Left Ventricular Structural Remodeling Induced by Hypertension - Xiaolin Wu; Qiaolan Wu; Lin Gao; Yu Lv; Zhichun Wu (Reviews in Cardiovascular Medicine, 2024)
Following long-term hypertension, mechanical stretching and neuroendocrine stimulation, cause multiple heterogeneous cells of the heart to interact, and result in myocardial remodeling with myocardial hypertrophy and fibrosis. The immune system, specifically macrophages, plays a vital role in this process. Macrophages are heterogeneous and plastic. Regulated by factors such as microenvironment and cytokines, polarization can be divided into two main forms: M1/M2, with different polarizations playing different roles in left ventricular structural remodeling associated with hypertension. However, descriptions of macrophage phenotypes in hypertension-induced myocardial hypertrophy models are not completely consistent. This article summarizes the phenotypes of macrophages in several models, aiming to assist researchers in studying macrophage phenotypes in hypertension-induced left ventricular structural remodeling models.